The impact of chemicals and additives on maize physiology and resistance to Spodoptera frugiperda - Basit, Abdul; Humza, Muhammad; Liu, Tong-Xian; Hou, Youming (Frontiers in Plant Science, 2026)
BackgroundSpodoptera frugiperda is a highly invasive pest that significantly threatens maize production globally. This work aims to report the physiological and biochemical impacts of different chemical treatments (DMSO, methyl oleate, DMF, xylene, uniconazole, azadirachtin, and chlorantraniliprole) on maize photosynthetic capacity and resistance response mechanisms from S. frugiperda.ResultsWe found a dose‐dependent effect on maize photosynthesis; lower concentrations of these chemicals promoted photosynthetic rate, whereas higher concentrations inhibited photosynthesis, especially in lower leaves. Mortality bioassays proved the dose-related response to the toxic potential of DMSO, DMF and xylene. However, the Y-tube bioassay revealed no remarkable changes in olfactory responses, thus indicating that the observed mortality was largely contributed by direct chemical toxicity rather than behavioral alterations. At the molecular level, cytochrome P450 genes (Sf CYP6AB12, Sf CYP6AE43, Sf CYP9A58 and Sf CYP9A59) were significantly overexpressed by chlorantraniliprole, and they were considered to be resistant genes against insecticides. Likewise, other compounds such as azadirachtin and uniconazole also selectively affected some P450 genes, providing additional evidence of the involvement of P450s in S. frugiperda metabolic resistance.ConclusionsThese results demonstrate the involvement of P450s in the development of insecticide resistance and suggest the importance of chemical dose on control of insect pests.